2022
DOI: 10.3892/ijo.2022.5400
|View full text |Cite
|
Sign up to set email alerts
|

Long non‑coding RNA CASC11 interacts with YBX1 to promote prostate cancer progression by suppressing the p53 pathway

Abstract: Prostate cancer (PCa) is one of the principal causes of cancer-related death worldwide. The roles and mechanisms of long non-coding RNA (lncRNA) involved in the development of PCa remain incompletely understood. The present study aimed to investigate the role and mechanism of lncRNA in PCa tumorigenesis. In the present study, lncRNA cancer susceptibility candidate 11 (CASC11) was revealed to be a crucial regulator of PCa progression. The expression profiles of CASC11 in PCa were identified through analysis of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…The development of high throughput sequencing technologies, together with the advances in computational pipelines, has led to an explosion in the discovery of disease-related lncRNAs. An increasing number of lncRNAs have been identified as crucial regulators of multiple diseases, including prostate cancer (9)(10)(11)(35)(36)(37). For example, Zhang et al (35) found that lncRNA DSCAM-AS1 was upregulated in prostate cancer, and promoted cancer progression by forming a positive feedback loop with forkhead box A1.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The development of high throughput sequencing technologies, together with the advances in computational pipelines, has led to an explosion in the discovery of disease-related lncRNAs. An increasing number of lncRNAs have been identified as crucial regulators of multiple diseases, including prostate cancer (9)(10)(11)(35)(36)(37). For example, Zhang et al (35) found that lncRNA DSCAM-AS1 was upregulated in prostate cancer, and promoted cancer progression by forming a positive feedback loop with forkhead box A1.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, lncRNAs were considered to be the byproducts of RNA splicing errors with no or limited physiological and pathological functions (9). With the rapid development of high-throughput sequencing technologies, an increasing number of lncRNAs have been found and identified as key regulators of biological and/or pathological behaviors during the occurrence and progression of numerous diseases, including prostate cancer, glioma, gastric cancer and cholangiocarcinoma (7,(9)(10)(11). For example, it has been reported that lncRNA 01614 promoted pancreatic cancer progression by suppressing GSK-3β (12).…”
Section: Vim-as1 Promotes Proliferation and Drives Enzalutamide Resis...mentioning
confidence: 99%
See 1 more Smart Citation